Immunological disturbance effect of exogenous histamine towards key immune cells - Yanan Liu; Huan Li; Chong Wang; Shanjun Chen; Renjie Lian; Weiqiang Wang; Linglin Fu; Yanbo Wang (Food Science and Human Wellness)
Histamine in food has attracted widespread attention due to the potential toxicity and associated health risk. However, its influences on immunological components, especially the function of key immune cells, are still poorly known. In this work, we explored the effects of exogenous histamine on the function of key immune cells such as intestinal epithelial cells, dendritic cells, and T cells. The results showed that histamine could affect the expression of allergy-related genes in CMT93 cells at a high dose of histamine. Moreover, it’s found that histamine could cause an imbalance in the levels of relevant immune factors secreted by dendritic cells and T cells, especially those related to allergy. At the same time, the proportion of MHC class Ⅱ-positive dendritic cells and the proportion of T helper 2 (Th2) cells in CD4+ T cells increased after histamine stimulation. We concluded that the presence of a certain level of histamine in food may affect the expression of allergy-related cytokines, disrupt the balance of the immune homeostasis, and potentially lead to adverse immune reactions. This work demonstrated the importance of including the estimation of histamine’s immune safety in aquatic products rather than merely considering the potential risk of food poisoning.